ประสิทธิผลของการใช้แนวปฏิบัติการจัดการทางการพยาบาลใน พระสงฆ์สูงอายุโรคความดันโลหิตสูง คลินิกสงฆ์อาพาธ โรงพยาบาลมหาราชนครเชียงใหม่ - ถนอมจิตร์ ปินตาปิน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Hypertension is a chronic disease commonly found in older monks. Nursing management is a method for controlling blood pressure. This operational study aimed to evaluate the effectiveness of nursing management guidelines implementation for older monks with hypertension receiving care at the outpatient monk clinic at Maharaj Nakorn Chiang Mai Hospital between March and June 2014. The study population consisted of 3 register nurses and 30 monks with uncontrolled hypertension. The first group of 15 patients received routine care that did not include the nursing management guidelines, while the remaining 15 patients received care based on the nursing management guidelines. Study instruments was Yodying’s Nursing Management Guidelines Among Elderly with Hypertension (2012). The effectiveness of the guidelines was evaluated based on clinical outcomes, including the proportion of older monks whose blood pressure could be brought under control, the nurses’ level of satisfaction with implementing the nursing management guidelines, and the older monks’ level of satisfaction with the treatment of their hypertension. Data were analyzed using descriptive statistics.